The Interrelationship Between FYN and miR-128/193a-5p/494 in Imatinib Resistance in Prostate Cancer - Ergün, Sercan; Akgün, Oğuzhan; Hekim, Neslihan Taşkurt; Aslan, Senanur; Ari, Ferda; Güneş, Sezgin; Abur, Ümmet (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: C-KIT is a receptor tyrosine kinase with oncogenic properties overexpressed in PCa cases. Through the use of an alternative promoter, a truncated c-KIT protein (tr-KIT) of 30-50 kDa is generated, lacking the extracellular and transmembrane domain. Tr-KIT promotes the formation of a multi-molecular complex composed of Fyn, Plcγ1, and Sam68. Imatinib blocks the activity of full-length c-KIT but has no effect on tr-KIT. LNCaP is the human PCa cell line that shows tr-KIT overexpression and PC3 does not show tr-KIT overexpression. miR-128/193a- 5p/494 are miRNAs targeting FYN, PLCγ1, and SAM68 combinatorially. The study's question is: can miR-128/193a- 5p/494 be related to imatinib resistance in PCa? Methods: LNCaP and PC3 cells were treated with imatinib in IC50 doses. Before and after imatinib administration, RNA was isolated and cDNA conversion was performed. By qPCR analysis, expression changes of tr-KIT specific pathway elements and miR-128/193a-5p/494 were analyzed before and after imatinib administration. Results: After imatinib administration, miR-128/193a-5p/494 were significantly overexpressed in LNCaP cells while downregulated significantly in PC3 cells (p<0.05). Also, FYN was upregulated in LNCaP cells (p<0.05) but there was no change in PC3 after imatinib administration. Conclusion: Especially upregulation of FYN may sponge miR128/193a-5p/494 and downregulate their transcriptional activity in LNCaP cells having tr-KIT activity. So, miR-128/193a-5p/494 may have a critical role in imatinib resistance via a tr-KIT pathway.
Keywords: truncated KIT (tr-KIT)